Analisis Pelanggaran Prinsip Dasar Etika Akuntan Pada PT. Asuransi Jiwasraya - Rosyta Pratiwi (Universitas 17 Agustus 1945, 2023)
An accountant must know the code of ethics because it is an important profession in the economic field. The accountant's code of ethics is used as a guide in carrying out its main duties and functions in accordance with the competence possessed by the accountant in order to improve the quality of his work so that it can be used as a guide in determining attitudes and behaving based on professional ethics. The development of today's technology, where there is a lot of competition, is actually more and more violations of professional ethics. Scandals that violate the code of ethics pose a serious problem for the ethical standards of the accounting profession. There are still many violations of professional ethics, in Indonesia one of which is PT. Asuransi Jiwasraya, which manipulated its financial statements. This case started that PT. Asuransi Jiwasraya stated that it was unable to pay the JS Savings Plan policy claim that was due in the amount of Rp. 802 billion on October 10 2018. From the results of the BPK investigation, it was revealed that there were inconsistencies which indicated fraud in the implementation of saving plans and investments. This analysis aims to explain the basic concepts of ethics, code of ethics, and find out which basic principles of accountant ethics have been violated by PT. Asuransi Jiwasraya. In the Case of PT. Asuransi Jiwasraya There are 4 basic principles of accountant ethics that have been violated, namely, integrity, objectivity, competence and prudence, and professional behavior.